Development of Optimization System of Two-stage Cylindrical Gear Standard Reducer - Wang Yong; Jiang Jing; Guo Gang; Pan Junyuan; Huang Taohong; Shi Wenjie (Jixie chuandong)
Based on the platform of Visual Basic 6. 0,Visual Fox Pro 6. 0 and Visual LISP,the optimal design system is developed by establishing mathematical model for optimization design of two- stage cylindrical gear standard reducer and using integer optimal method and visual combination software development technology. The system consists of several exe executable programs and lsp program. Under the control of internal interface program,the system can realize optimization design and gear parts drawing.